PENETAPAN BATAS DESA SECARA KARTOMETRIK (Studi Kasus di Kecamatan Bantul dan Kecamatan Bambanglipuro) - , GOGO MATONDI RAMBE, Ir. Sumaryo, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Delimitation of villages boundary in Indonesia is carried out to meet the needs of the village boundary geospatial data in an orderly and coordinated. Delimitation of the village boundary by carthometric method done in order to accelerate the process of delimitation and demarcation of the village boundary. Project conducted is the first project organized by the Geospatial Information Agency in Bantul Regency, Yogyakarta. This project aims to create a map of the boundary villages in the villages in sub-district of Bantul and Bambanglipuro. The materials used in this project is a RBI map in digital format, satellite imagery of sub-districts Bantul and Bambanglipuro, Interior, The regulation of Ministry of Home Affairs number 27 of 2006, and the villages maps are used as reference village boundaries. The materials collected and created map working that used to draw a line on a map by carthometric method in the map working. Map created using sub-districts of Bantul and Bambanglipuro image that has been corrected and a RBI map , which has such a village indicative boundaries. Withdrawal of the boundary line on a map of the work follows the boundary of the village on the old map with the interpretation of the objects on the map of the existing work. Results delimitation boundary by carthometric method in the district of Bantul and Bambanglipuro are maps of village boundary in the Bambanglipuro and Bantul sub district. Village boundary maps generated from these activities serve as a map of the village administrative boundaries that can be used as a boundary of village authority to regulate their own regions.